The Implementation of Multicultural Education Values in Learning Dhomir, Fiil Madhi and Mudhori’ for Students Nur Al-Maarif Islamic Boarding School - Helty, Helty; Rahmadani, Alvie; Amelia, Nova; Rahmanda, Rahmanda (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
This research explains the application of multicultural education values in learning Arabic, especially in grammatical concepts such as Dhamir, Fi'il Madi, and Mudhori' at the Nur Al Maarif Islamic Boarding School. The focus is integrating multicultural values into Arabic language learning as an effort to increase students' understanding of the values of diversity. This research uses a qualitative method with a case study approach, involving observations and interviews with Civir class students (class 0) to evaluate the success of implementing the learning method. The results of the research show that the integration of multicultural education values in learning Arabic grammar makes a significant contribution to increasing students' understanding and forming an attitude of respect for diversity. The learning method uses a mawdui approach or thematic interpretation of Al-Quran verses related to multicultural education. This research documents a teaching process that strengthens student understanding and promotes the values of diversity in the Islamic boarding school environment.